INHIBITORY TEST OF FLAVONOID PROPOLIS KELULUT EXTRACTS (G. thorasica) ON Porphyromonas gingivalis AS AN ETIOLOGIC FACTOR OF CHRONIC PERIODONTITIS - Valentina, Ursula; Oktiani, Beta Widya; Panjaitan, Fransiska Uli Arta (FKG Unlam, 2019)
Background: Natural ingredients have been used recently for its ability in curing various diseases and reducing the risk of antibiotic resistance. One of these natural ingredients is propolis. Bee propolis Geniotrigona thorasica from South Kalimantan has a strong antibacterial activity with active compounds such as flavonoids. Flavonoids can damage cell membranes and can fight the expansion of Î²-lactamase enzyme produced by gram-negative bacteria. Porphyromonas gingivalis is a gram-negative bacterium that causes chronic periodontitis with a prevalence of 80%. Objective: This study was to find out the inhibitory test of flavonoid propolis kelulut extract at the concentration of 0.1%; 0.3% and 0.5% on Porphyromonas gingivalis bacteria. Method: This type of research used a pure experimental method with post-test only and control group design. One-way ANOVA statistical test was performed with follow-up test of Post Hoc Dunnetâ€™s T3. Treatment was given to 4 groups with 5 repetitions. Observations were carried out using digital calipers in all groups after incubation for 24 hours with a temperature of 37â„ƒ. Results: One Way Anova and Post Hoc Dunnet's T3 showed significant differences in the diameter flavonoid propolis extract inhibitory zone against Porphyromonas gingivalis. The average value of Flavonoid extract inhibitory zone after 24 hours observation with a concentration of 0.5%; 0.3%; 0.1% and sterile distilled water were 25.24 mm; 18.04 mm; 13.58 mm and there was no inhibitory zone observed in sterile distilled water group. Conclusion: Extract of flavonoid propolis kelulut at the concentration of 0.1%; 0.3% and 0.5% can inhibit the growth of Porphyromonas gingivalis as an etiologic factor of chronic periodontitis.